Airway resistance measured by the interrupter technique: normative data for 2–10 year olds of three ethnicities. Issue 3 (1st September 2002) - McKenzie, S A; Chan, E; Dundas, I; Bridge, P D; Pao, C S; Mylonopoulou, M; Healy, M J R
Abstract : Background and Aims: The measurement of airway resistance using the interrupter technique (Rint ) is feasible in preschool children and other subjects unable to undertake spirometry. This makes it potentially useful for the measurement of lung function in these groups. Commercial devices use different algorithms to measure pressure and flow from which Rint is derived. This study provides normative values for British children using devices from a single manufacturer. Methods: Rint was measured in 236 healthy children of three ethnic groups (Afro-Caribbean and black African, Bangladeshi, and white British) aged 2–10 years using Micro Medical devices. Software in the devices calculated Rint from pressure measured by the two point, back extrapolation method from the pressure transient during valve closure, with flow measured just before valve closure. Results: Rint is related to both age and height, but when age is allowed for there is not a significant relation with height. Neither gender nor any of the ethnicities studied was significantly related to Rint . Discussion: These measurements in healthy children using this technique may be used as reference data for similar populations.